In pursuit of a high-temperature, high-pressure, high-viscosity standard: the case of Tris(2-ethylhexyl) Trimellitate - Wakeham, William A. (2017)
This paper presents a reference correlation for the-viscosity of tris(2-ethylhexyl) trimellitate designed to serve in industrial applications for the calibration of viscometers at elevated temperatures and pressures such as those encountered in the exploration of oil reservoirs and in lubrication. Tris(2-ethylhexyl) trimellitate has been examined with respect to the criteria necessary for an industrial standard reference material such as toxicity, thermal stability, and variability among manufactured lots. The viscosity correlation has been based upon all of the data collected in a multinational project and is supported by careful measurements and analysis of all the supporting thermophysical property data that are needed to apply the standard for calibration to a wide variety of viscometers. The standard reference viscosity data cover temperatures from 303 to 473 K, pressures from 0.1 to 200 MPa, and viscosities from approximately 1.6 to 755 mPa s. The uncertainty in the data provided is of the order of 3.2% at 95% confidence level, which is thought to be adequate for most industrial applications.